Sustainability skills disclosure for boards: An essential prerequisite for assessing sustainability competence - Gül Demirtaş; Christian Strenger; Tobias Tröger (Leibniz Institute for Financial Research SAFE, 2024)
Not only institutional investors are increasingly demanding to know more about the sustainability skills of the boards they elect. These skills demonstrate a company's capability to navigate new regulations and meet self-imposed targets. Consequently, they also serve as a significant proxy for a firm's commitment to pursuing transition strategies, providing a bonding mechanism. In response to the growing demand for transparency, Germany has recently set itself apart with its German Corporate Governance Code (GCGC) recommendation that companies show their boards' sustainability expertise by disclosing a skills matrix. We analyze the board skills disclosures for the supervisory boards of the leading German listed companies for 2022, the first year after the adoption of the recommendation. We compare these disclosures with those of companies from France, a country that has long expressed sustainability-related expectations for company boards but has yet to make any recommendations for the disclosure of sustainability skills. We observe that German companies follow a more uniform approach to reporting directors' sustainability skills. However, the lack of a standardized definition of sustainability expertise in both countries has resulted in significant variations in how companies define this essential disclosure item, thereby reducing the comparability of the reported data. We recommend that policymakers specify skills disclosure rules for directors and director nominees more granularly, including a standardized definition of sustainability expertise, and that they support them with effective enforcement mechanisms, reinforced by external audits and government oversight.
Keywords: G34; G39; K2; M14; 330; coporate governance; corporate boards; sustainability skills; disclosure; ESG